Prevalence of Risk Factors of Coronary Artery Disease among Women - Issac, Reena (Indian Journal of Nursing Sciences, 2024)
Aim: Coronary artery disease (CAD) is one of the major causes of death worldwide. This study aimed to determine the prevalence of risk factors of CAD among women. Materials and Methods: A descriptive survey design was used to collect data from women (35–55 years) residing in a selected community in Kerala, India. Results: Majority of the women (35.3%) were between 35-39 years, 63.7% were educated up to 10th standard and 55.9% were household workers. In the present study, unhealthy dietary practices were reported among 35.0% of women, inadequate physical activity was prevalent among 72.5% and moderate or severe stress was observed among 75.4% of women. Majority of the women (63.7%) had obesity (BMI≥25Kg/ m2 ) and 87.3% had (WC ≥80cms) in the present study. Among the study subjects, 63.7% had overweight (>25Kg/m2 ) 87.3% had abdominal obesity (≥80cms). The present study reports that 19.6% of women had a systolic blood pressure ≥140 mm of Hg and 22.5% had a diastolic blood pressure of ≥90 mm of Hg. This study reports that the fasting blood sugar level of 37.2% of women was above 100mg% and among that 12.7 % had FBS ≥126mg% also observed that 39.2% of women had high total cholesterol levels (>200mg%). Conclusion: Risk factor identification is the key to prevent CAD.